Pengaruh Penggunaan Sapaan Keluarga Terhadap Identitas Budaya Mahasiswa Tionghoa Batam - Winnie Cherina (STAI Darul Kamal NW Kembang Kerang, 2026)
This study aims to examine the influence of the use of Chinese kinship terms on the ethnic and cultural identity of Chinese students in Batam. A quantitative approach was employed using purposive sampling, involving 139 respondents. Data were analyzed using Spearman correlation and linear regression. The results indicate a positive and significant relationship between the use of kinship terms and cultural identity (r = 0.383; p < 0.001). Regression analysis revealed that language usage has a significant influence, contributing 10.6% to the outcome. These findings indicate that the use of kinship terms plays a role in shaping cultural identity, although it is not the sole influencing factor